Quality of Service Comparison of DSDV and DSR Routing Protocols for V2V Communication in VANET - bintoro, ketut bayu yogha; Mukholladun, Muhammad Wildan (Universitas Andalas, 2024)
The study evaluates the Quality of Service (QoS) performance of the Destination-Sequenced Distance Vector (DSDV) and Dynamic Source Routing (DSR) protocols in vehicle-to-vehicle (V2V) communication within a Vehicular Ad-Hoc Network (VANET) environment. Simulations were conducted to analyze key QoS metrics, including throughput, delay, and routing overhead, under various traffic densities and network dynamics. The results reveal that DSR excels in scenarios with rapid topology changes due to its lower routing overhead. At the same time, DSDV provides better route stability in less dynamic conditions, ensuring consistent performance. These findings underscore the importance of matching routing protocols to the specific requirements of V2V applications, such as real-time data exchange or traffic safety, to ensure informed decision-making. The study also highlights the potential for a hybrid protocol that integrates the stability of DSDV with the efficiency of DSR to address diverse VANET challenges and enhance overall QoS performance